METHODS OF INCREASING AND DEVELOPING SPEAKING SKILLS OF MILITARY SERVANTS IN THE PROCESS OF MILITARY EDUCATION - XAYDAROV. F.I; ROZIMOVA Y.Y (Scholar Express Journal, 2021)
This article is about the culture of the speech, elocution and the history of the speech, communicative aspects of the speech, speech etiquette and standards of literary language. Besides, in this article is spoken about important aspects of well-bred speech formulation in professional human activity
Keywords: Speech; oratory; the culture of the speech; communication of the speech